Asteroseismology of exoplanet host stars. Issue Volume 11:Issue A29B(2015) (27th October 2016) - Huber, Daniel
Abstract: Asteroseismology is among the most powerful observational tools to determine fundamental properties of stars. Space-based photometry has recently enabled the systematic detection of oscillations in exoplanet host stars, allowing a combination of asteroseismology with transit and radial-velocity measurements to characterize planetary systems. In this contribution I will review the key synergies between asteroseismology and exoplanet science such as the precise determination of radii and ages of exoplanet host stars, as well as applications of asteroseismology to measure spin-orbit inclinations in multiplanet systems and orbital eccentricities of small planets. Finally I will give a brief outlook on asteroseismic studies of exoplanet hosts with current and future space-based missions such as K2 and TESS.